Relationship between Introversion and Extroversion Personality and Learning Styles of UPSI Student - Mohd Yunos, Faza Reza; Husin, Mohd Razimi (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2021)
This research is conducted to identify the Relationship between Introversion and Extroversion Personality with Learning Style of UPSI students. This research is conducted to identify the relationship of the Introversion and Extroversion personality affect the by the Visual, Auditory and Kinesthetic (VAK) learning style. In addition, suitable activities are also discussed to suit the needs of introversion and extroversion personality. A total of 233 second year UPSI students were selected in this research. The data was collected using questionnaire and divided into two parts. The first part is the identification of the introversion and extroversion personality of the respondent and the second part is the learning style of the respondent which are divided into 3 parts which are Visual, Auditory and Kinesthetic. The data collected was then analysed using Pearson Correlation test. The Pearson Correlation test shows no significant between the introversion and extroversion personality of the respondent and the VAK learning style due to the p=.730. Suitable activities consist of hands-on and group activities is among the major suggestion collected from the respondent. In conclusion, although there is no significant between Introversion and Extroversion personality and VAK learning style, the teacher should pay attention to their students’ behavior in a learning environment to ensure the engagement of the students towards the lesson taught by them